Pengaruh Perbedaan Bahan Pengemas Terhadap Mutu Sensoris Amplang Selama Penyimpanan - Nova Zulfahmi, A.; Martanto, Martanto; Cholid, Irfan; Dwi Hastuti, Ningrum (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2021)
The decrease in purchasing power of the community has led to many unsold amplang crackers, which often suffer from physical and sensory damage. Physical damage includes a loss of crispy texture, while sensory damage includes a stale aroma and taste, as well as a brownish appearance. To prolong the shelf life of amplang crackers, packaging is needed. The packaging materials used in this study are PP, PET, and aluminum foil. The objective of this research is to determine the effect of different packaging materials on the sensory quality of amplang crackers during storage. The results show that in the sensory test, aluminum foil packaging received the highest score for aroma, which was 6.5, indicating a preference. The taste parameter also scored the highest with aluminum packaging, at 6.5. Meanwhile, the texture and color parameters obtained the best scores with aluminum packaging, with scores of 6.8 and 7.5, respectively. In conclusion, the research finds that aluminum foil packaging is the best way to maintain the sensory quality of amplang crackers during a 40-day storage period.